Design Aspects of Scanning Receiver Systems - Mzyk, Raphael; Dehm-Andone, Gunther; Langmann, Frank; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (IEEE German Microwave Conference, 2012)
In this paper, a cost-effective approach on receiver systems for frequency scanning and direction finding applications is presented. It consists of a hybrid analog topology, combining direct sampling and double superheterodyne architecture, as well as a scalable digital platform that offers multi channel data aquisition requiring minimum hardware ressources. The receiver front-end covers the VHF (very high frequency) and UHF (ultra high frequency) band from 30MHz to 3GHz while a 50MHz instantaneous bandwidth can be processed. Key modules like a reconfigurable filter and low noise PLL (phase-locked loop) as well as a digital platform are highlighted and the trade-off between cost effectiveness and performance is investigated.
elib2cris::1512001600,mzyk2012
Keywords: Scanning receiver; frequency synthesis; reconfigurable filter; multi channel receiver